Forests-a Viable Option For Mitigating Climate Change - Gupta, Meenakshi; Saleem, M.; Gupta, L. M. (Indian Forester, 2009)
Forests contribute to global climate change through their influence on the global carbon (C) cycle. The world's forests store an estimated 536 Giga tons of Carbon (GtC) in biomass, 1104GtC in soils (to a depth of 3m) and additional amounts in dead organic matter pools, including fine and coarse woody debris. Accounting for the imbalance in the global C cycle suggests that forests are not significantly contributing to the net increase in atmospheric CO2 and thus not playing a major role in global climate change. But this may not continue into the future as temperate and boreal forests reach maturity and become a smaller C sink, and if rates of tropical deforestation and degradation continue to accelerate. Mitigation options by the forestry sector include extending carbon retention in harvested wood products, product substitution, and producing biomass for bio-energy. Aggressive adoption of these forest management options are necessary to prevent forests from becoming a significant net source of CO2 to the atmosphere in the future and contributing to climate change.